Problem dan Solusi Studi Mahasiswa Semester Tua - Raharjo, Raharjo (NADWA, 2014)
This paper describes the problems of old-semester students in completing their study at the Faculty of Science of Islamic Education and Teaching (FITK) IAIN Walisongo Semarang. The study of exploratory qualitative approach involves 20 students from all courses taken by purposive random sampling with the tech-nique of questionnaires, interviews and documentations. The results are: (1) The problems faced by elderly semester students is a matter of academic and non-academic, namely working part time, participating organizations, teaching and unwarranted. (2) The problems are handled by the leaders of the faculty in-volved: (a) anticipatory since the beginning of their study and academic orienta-tion; (b) preventing for their study by the lecturer as supervisor; and (c) curating towards the end of the study by the head of the faculty. These steps are per-formed in order to provide opportunities for students to be able to pass and not threatened to drop out.